2017
DOI: 10.1055/s-0036-1588825
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient and Concise Synthesis of N-3-Substituted 9-Methoxy-4H-[1]-benzopyrano[2,3-d]pyrimidine-4(5H)-imines and Form­amidine Derivatives from Methyl N-(3-Cyano-8-methoxy-4H-[1]-benzopyran-2-yl)methanimidate

Abstract: A four-step microwave-assisted reaction of N-3-susbstituted 4H-[1]-benzopyrano[2,3-d]pyrimidine-4(5H)-imines and formamidine derivatives was successfully developed from primary amines, cyclic secondary amines, and methyl N-(3-cyano-8-methoxy-4H-[1]-benzopyran-2-yl)methanimidate as key intermediate. The simplicity of the microwave protocols gave facile possibilities of isolation of the desired products by simple filtration. The synthesized compounds were obtained in good yields and purity, and characterized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Compounds as 2-imino coumarin-3-carbonitrile 3(a-d) and 2-amino-4 H -chromene-3-carbonitrile 4(a-d) were synthesized according to methods previously developed in our laboratory and described in the literature [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compounds as 2-imino coumarin-3-carbonitrile 3(a-d) and 2-amino-4 H -chromene-3-carbonitrile 4(a-d) were synthesized according to methods previously developed in our laboratory and described in the literature [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The structure assignment of co pound 10 was evidenced by FTIR (C=N stretch, 1615 < ν < 1645 cm −1 ), by 1 H NMR for With the underlying idea to introduce the pyrimidine fragment on 4H-chromene skeleton, it is necessary to add an electrophilic carbon to the 2-amino function of 4Hchromene-3-carbonitrile 4 for hetero cyclization. For this, the transformation of the 2-amino function of 4 into imidate 6 works well by the addition of 6 equivalents of ethyl orthoformate 5 at 110 • C under microwave dielectric heating [20] for 60 min catalyzed with glacial acetic acid 0.5% mol., which afforded the desired functionalized imidate 6 (Table 1) in moderate (6c: 52%) to good yields (6d: 90%). The interest of this method is that compound 6 is not soluble in the reaction mixture, which facilitates recovery using simple filtration.…”
Section: Synthesis Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the potential pharmacological interest of the 2-amino-4H-chromene-3-carbonitrile platform (Figure 1), we were motived in our laboratory to explore the chemical reactivities of the carbonitrile function (electrophilic center) and the 2-amino group (nucleophilic center) for the construction of new heterocycle derivatives in combination to exploration of biological activities, such as their antiproliferative activities on tumor cell lines or inhibition activities of protein kinases (PKs) in a preliminary approach. In previous works, we showed that this platform (Figure 2) offers the possibilities to built tricyclic compounds (A) 11 , amidines (B) 12 and N-aryl derivatives (C) by trans-imination of 2-imino-precursors 13 . In continuation of these works, we decided to explore now the construction of N-benzyl derivatives (D) of 2amino-4H-chromene-3-carbonitrile, which are potentially the mono N-alkylated compounds of this platform using various benzyl halides.…”
Section: Figure 1: Bioactive 2-amino-4h-chromene Derivatives Reported...mentioning
confidence: 97%